Learning Organization Sebagai Prediktor Kesiapan Berubah Organisasi - Audia Junita; Muhammad Hermansyur (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
As a public service organization, health center changes required to provide quality health services to the community better. One of the factors that affect the formation of organizational readiness for change is a learning organization. Ideally a learning organization can be a learning facility for its members on an ongoing basis and may direct the member to keep the environment abreast. The transform research is performed to assess whether the health center in the city of Medan has been transformed into a learning organization and how it affects the formation of learning organization change readiness of the organization. This research was the study of causality. Location of the study conducted in 13 health centers Inpatient scattered in the district in the city and sample Medan. Population of health workers in health centers is as much as 195 respondents. Data sourced from primary data and were collected using a questionnaire. The analysis technique used is regression technique. The research proves that the health center in the city of Medan has become a form of organizational learning organizations that do good, so too has the readiness to turn into public service organizations in the health sector in accordance with the demands of the times. Dimensions of organizational learning simultaneously changed significantly influence organizational readiness; with dimensions connecting the organization to its environment is the most dominant influence in shaping the organization's readiness for change.